Age Patterns of Fertility in Sri Lanka - Prakasam, C.P. (NARESA:Colombo, 1984)
To examine the age patterns of fertility in Sri Lanka,ASMR,ASMFR,indexed marital fertility schedules and estimated natural fertility schedules deruved from the m(a)has been calculated by using the method suggested by Coale and Trussel(1974).To examine the effects of nuptiality change and contraceptive practice If,Im and Ig have been calculated for the census periods 1953,1963,1971 and 1981 at district level.The analysis revealed that changes in proportion of never married women had a greater impact on fertility decline than changes in marital fertility.
Keywords: Natural Fertility; Marital Fertility; Health Sciences